The Concept of Sufism Education From the Perspective of Sheikh Abdurrauf As-Singkily in the Book Al-Mawa’iz Al-Badi’ah - Dinda Helmi Kayana Juwita; Ismail Marzuki Hasibuan; Mulia Sari (P3M IAI Nusantara Batang Hari, 2023)
Sufism education is the most fundamental education in shaping noble personalities. The moral decline of modern humans today makes their lives undirected, reckless and bad. For this reason, we need to elaborate on the thoughts of previous scholars to fortify the moral decline that is happening today. Sheikh Abdurrauf as-Singkili said, no knowledge is perfect but with the perfection of one's morals. The purpose of this research is to describe the concept of Sufism education from Abdurrauf as-Singkili's perspective in the book al-mawaizul al-badi'ah. This research is a library research. By using analytic descriptive method. The analysis technique used is content analysis, which is a research technique that concentrates on real content. The results of this study show a number of findings, namely the basic concept of Sufism education according to Abdurrauf as-Singkili is an effort to foster noble behavior, both to Allah SWT, self, and fellow humans. This is a concept of Sufism that will produce noble attitudes, which are very important to implement as an effort to foster good behavior (moral). Keywords: Abdurrauf, Sufism Education, Mawa'izhul Badi'ah